2009
DOI: 10.1097/aco.0b013e32832972f3
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric laryngospasm: prevention and treatment

Abstract: Identifying the risk factors and taking the necessary precautions are the key points in prevention of laryngospasm. An experienced anesthesiologist is associated with lower incidence of laryngospasm. Airway management is the most essential part of treatment of laryngospasm. Drugs can be used as an adjunct in treatment of laryngospasm, especially when anesthesia is administered by beginners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(30 citation statements)
references
References 109 publications
0
24
0
4
Order By: Relevance
“…The number of participants needed for the study was determined according to the proportions described by El-alami et al 2 , who reported that the incidence of laryngospasm dur-ing adenotonsillectomy could reach 27%, and Nascimento et al 5 , who reported that respiratory complications occurred in 43% of children showing any pre-operative symptoms related to airway disease. Assuming an average value for this incidence and defining the errors of the hypothesis as β = 0.8 and α = 0.05, we established the minimum number of participants to be 180 and divided them into 2 groups for the study.…”
Section: Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of participants needed for the study was determined according to the proportions described by El-alami et al 2 , who reported that the incidence of laryngospasm dur-ing adenotonsillectomy could reach 27%, and Nascimento et al 5 , who reported that respiratory complications occurred in 43% of children showing any pre-operative symptoms related to airway disease. Assuming an average value for this incidence and defining the errors of the hypothesis as β = 0.8 and α = 0.05, we established the minimum number of participants to be 180 and divided them into 2 groups for the study.…”
Section: Statisticsmentioning
confidence: 99%
“…The factors that increase the risk of laryngospasm include: small children, endotracheal intubation, inhalation anesthesia, inadequate anesthesia depth, respiratory infections and the presence of secretions in the pharynx. Treatment consists of increasing the pressure in the airway with a face mask, which can cause regurgitation, and administering succinylcholine, a drug that can trigger allergic reactions, cardiac arrhythmias, rhabdomyolysis and malignant hyperthermia 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…as decades premature [2], I agree that any renewed prediction of the demise of suxamethonium may again be premature, even…”
Section: A Replymentioning
confidence: 90%
“…In regional anaesthesia, performing a nerve block on the incorrect side is a rare event, but a very serious error. The use of peripheral nerve blocks is increasing and subsequently so are the number of incorrect site incidents [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation